2020
DOI: 10.3390/ijms21020461
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Molecular Basis of the Noonan Syndrome-Causing Mutation T42A of SHP2

Abstract: Noonan syndrome (NS) is a genetic disorder caused by the hyperactivation of the RAS-MAPK molecular pathway. About 50% of NS cases are caused by mutations affecting the SHP2 protein, a multi-domain phosphatase with a fundamental role in the regulation of the RAS-MAPK pathway. Most NS-causing mutations influence the stability of the inactive form of SHP2. However, one NS-causing mutation, namely T42A, occurs in the binding pocket of the N-SH2 domain of the protein. Here, we present a quantitative characterizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 21 publications
0
14
1
Order By: Relevance
“…Despite their abundance in the proteome, our knowledge about the folding mechanism of SH2 domains is very limited, with only few experimental data available. [33][34][35][36][37][38] Given their key role in cell physiology and their involvement in several human diseases, understanding the determinants of SH2 domain stability, strictly correlated with proper folding and accurate function in the recognition of specific ligands, appears a fundamental task to complete. To achieve this goal, a powerful methodology to determine the biophysical properties of a given protein system relies in its comparison with other proteins belonging to the same family, generally characterized by similar topology and function but with different primary structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite their abundance in the proteome, our knowledge about the folding mechanism of SH2 domains is very limited, with only few experimental data available. [33][34][35][36][37][38] Given their key role in cell physiology and their involvement in several human diseases, understanding the determinants of SH2 domain stability, strictly correlated with proper folding and accurate function in the recognition of specific ligands, appears a fundamental task to complete. To achieve this goal, a powerful methodology to determine the biophysical properties of a given protein system relies in its comparison with other proteins belonging to the same family, generally characterized by similar topology and function but with different primary structures.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their abundance in the proteome, our knowledge about the folding mechanism of SH2 domains is very limited, with only few experimental data available 33–38 . Given their key role in cell physiology and their involvement in several human diseases, understanding the determinants of SH2 domain stability, strictly correlated with proper folding and accurate function in the recognition of specific ligands, appears a fundamental task to complete.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of the structural distribution of T42, T52, I56, L65 and L88 residues reveals that they are all physically located in the binding pocket of the N-SH2 ( Figure 2). Recently we characterized the effect of the T42S mutation (together with the Noonan Syndrome causing a mutation of T42A) on the binding kinetics between N-SH2 and Gab2 608-620 [29]. A structural analysis performed by homology modelling suggested that the polar -OH group of the side chain of T42 may have the role to partially shield the negative charge of phospho-tyrosine, thus affecting the rate of release of the ligand without affecting the negative charge of the phospho-tyrosine to be in direct contact with positively charged side chains in the binding pocket.…”
Section: N-sh2 Shp2: Gab2 Complex Is Stabilized By Weak Interactionsmentioning
confidence: 99%
“…Although their fundamental role for the physiology of the cell and their involvement in several molecular pathways, only few experimental works characterized the folding properties of SH2 domains. 10,13,[18][19][20][21] Understanding the determinants of thermodynamic stability as well as characterizing the folding pathway of a protein is of fundamental importance to depict the molecular basis of its biochemical function. Moreover, a structural characterization of the transition state(s) and of possible intermediates along the folding reaction allows to pinpoint potential aberrant misfolding events, that may result in protein misfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Although their fundamental role for the physiology of the cell and their involvement in several molecular pathways, only few experimental works characterized the folding properties of SH2 domains 10,13,18–21 . Understanding the determinants of thermodynamic stability as well as characterizing the folding pathway of a protein is of fundamental importance to depict the molecular basis of its biochemical function.…”
Section: Discussionmentioning
confidence: 99%